2017
DOI: 10.1021/jacs.7b08523
|View full text |Cite
|
Sign up to set email alerts
|

Nanobubbles: An Effective Way to Study Gas-Generating Catalysis on a Single Nanoparticle

Abstract: Gas-generating catalysis is important to many energy-related research fields, such as photocatalytic water splitting, water electrolysis, etc. The technique of single-nanoparticle catalysis is an effective way to search for highly active nanocatalysts and elucidate the reaction mechanism. However, gas-generating catalysis remains difficult to investigate at the single-nanoparticle level because product gases, such as H and O, are difficult to detect on an individual nanoparticle. Here, we successfully find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 64 publications
1
97
1
2
Order By: Relevance
“…Detailed hydrogen bubble formation in the hollow polymer vesicles is unclear since there are only few theoretical studies about nanobubble nucleation and formation for nanochannels or nanospaces. [49][50][51] Although there is a high possibility that nanobubbles might be generated on Pdots with the assistance of remaining free amphiphilic surfactant in solution, 52 Pdot photocatalysts can be reactivated for hydrogen generation by degassing the system with Ar. This proves that the deactivation process is actually caused by generated hydrogen.…”
Section: Photocatalytic Experiments Of Hollow Structuresmentioning
confidence: 99%
“…Detailed hydrogen bubble formation in the hollow polymer vesicles is unclear since there are only few theoretical studies about nanobubble nucleation and formation for nanochannels or nanospaces. [49][50][51] Although there is a high possibility that nanobubbles might be generated on Pdots with the assistance of remaining free amphiphilic surfactant in solution, 52 Pdot photocatalysts can be reactivated for hydrogen generation by degassing the system with Ar. This proves that the deactivation process is actually caused by generated hydrogen.…”
Section: Photocatalytic Experiments Of Hollow Structuresmentioning
confidence: 99%
“…With DFM, Li et al reported previously that the formation of surface nanobubbles leads to at ime-dependent scattering intensity change of the single NP catalyst. [13] Here,with HSLDFM and the rotation sensing of asingle AuNR, we monitored the Pt-catalyzed decomposition of H 2 O 2 .W eu sed 40 nm 96 nm AuNR@PtNDs (Nanoseedz), where the AuNR surface is decorated by 3nmP t nanodots.T ransmission electron microscopy (TEM) results indicated that the NRs are monodisperse and uniform in size. UV/Vis spectroscopy showed their extinction maximum is at % 740 nm.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…It is hard to reuse and recycle the catalysts for the whole reaction. Compared to the homogeneous catalysts, the heterogeneous catalysts are easy for reusing and recycling and are friendly to the environments [16][17][18][19] . The noble metal based heterogeneous catalysts have been proven active in producing hydrogen from FAD under mild conditions, among which Pd based heterogeneous catalyst are found especially effective.…”
Section: Introductionmentioning
confidence: 99%